2017
DOI: 10.1080/14756366.2017.1380637
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity analyses of γ-benzylidene digoxin derivatives to different Na,K-ATPase α isoforms: a molecular docking approach

Abstract: Digoxin and other cardiotonic steroids (CTS) exert their effect by inhibiting Na,K-ATPase (NKA) activity. CTS bind to the various NKA isoforms that are expressed in different cell types, which gives CTS their narrow therapeutic index. We have synthesised a series of digoxin derivatives (γ-Benzylidene digoxin derivatives) with substitutions in the lactone ring (including non-oxygen and ether groups), to obtain CTS with better NKA isoform specificity. Some of these derivatives show some NKA isoform selective eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
1
13
1
3
Order By: Relevance
“…We propose that this increase is possible due to the higher binding affinity of digoxin and BD-15 to the α1 and α3 isoforms of Na,K-ATPase, promoting changes in structure on the Na + binding site of Na,K-ATPase that may accelerate the access and binding of the cation to the enzyme, resulting in higher Na,K-ATPase cycling and activity. 36 Our data corroborated with Oselkin et al 11 that demonstrated the increase of activity in Na,K-ATPase after ouabain treatment, digoxin, and marinobufagenin at nanomolar concentrations in hippocampal slices in culture; the increase of this activity in rats treated with intraperitoneal injection of digoxin was also observed. Gao et al 41 demonstrated the Na,K-ATPase activity increase in ventricular myocytes extracted from guinea pigs and canines, showing a direct effect of ouabain in the nanomolar range.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We propose that this increase is possible due to the higher binding affinity of digoxin and BD-15 to the α1 and α3 isoforms of Na,K-ATPase, promoting changes in structure on the Na + binding site of Na,K-ATPase that may accelerate the access and binding of the cation to the enzyme, resulting in higher Na,K-ATPase cycling and activity. 36 Our data corroborated with Oselkin et al 11 that demonstrated the increase of activity in Na,K-ATPase after ouabain treatment, digoxin, and marinobufagenin at nanomolar concentrations in hippocampal slices in culture; the increase of this activity in rats treated with intraperitoneal injection of digoxin was also observed. Gao et al 41 demonstrated the Na,K-ATPase activity increase in ventricular myocytes extracted from guinea pigs and canines, showing a direct effect of ouabain in the nanomolar range.…”
Section: Discussionsupporting
confidence: 92%
“…Previous works from our group 36 F I G U R E 9 Production of H 2 O 2 and SOD activity of N2a cells after ischemia. N2a cells were induced to chemical ischemia and treated with digoxin, CTS for 5 hours and reperfused with cell culture medium for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its derivatization usually leads to a reduction in the NKA inhibitory effects of the resulting derivative, both in the case of double bond saturation and cycle opening [ 138 , 139 ] as well as by the introduction of a benzylidene group at the C-21 position [ 140 , 141 ]. However, in some cases, this modification resulted in a change in the CS affinity for the individual NKA isoforms [ 142 ]. This fact was also confirmed by the work of [ 143 ], who reported on specific inhibition of the α-4 isoform of NKA caused by a newly prepared derivative of compound 1 , in which the lactone group was replaced by a benzotriazole moiety, and whose IC 50 on NKA (α-4 isoform) was three orders of magnitude lower than that for compound 1 .…”
Section: Regulation Of Na + /K + -Atpase Activitymentioning
confidence: 99%
“…These cases involved particularly the introduction of a benzyl group at the C-21 position of Dg . The benzyl group was subsequently substituted by short non-oxygen and ether groups and depending on the type of the attached substituent, there were changes in compound selectivity (almost over 100% in case of non-oxygen derivative) for NKA isoforms α1, α2, α3 [ 70 ]. Syeda et al went even further and decided to replace the entire furanone cycle of ouabain with a triazole, to which various hydrocarbon residues were attached at the N-1 position of the triazole ( Figure 9 ).…”
Section: Na + /K + -Atpase Binding Of Cardiac Glycosidesmentioning
confidence: 99%